Elizabeth Bishop and the vilanelle - Gadpaille, Michelle (Primerjalna književnost, 2019)
The genesis of this study lies in Elizabeth Bishop's famous poem, "One Art." A villanelle, it stands out luminously against the background of contemporary poetics: the lingering legacy of modernist free verse and the many branches of experimental post-modernist poetry in the United States. It stands apart, with Theodore Roethke among the few precursors, claiming a traditional fixed poetic form - the 6-stanza villanelle - as a valid medium for expressing the late-20th century concerns of a scholarly, peripatetic, lesbian poet. Formally, it is an anachronistic appropriation; aesthetically, it is a triumph. The questions triggered by Bishop's poem and explored by this paper are three-fold: first, the adequacy of existing terminology for defining the refrain, where we propose the need for a new term: polysemic repetend. Our second question addresses the perceived global influence of "One Art". We then turn to the presence of the villanelle in Slovene poetics and consider how Bishop has been translated, since we assume that the formal complexity of the metrical and rhyme arrangement will present a challenge for the translator (Veno Taufer). The study thus works towards a modest appreciation of parallel New Formalist aesthetics between American and Slovene poetry.
Keywords: ameriška književnost; ameriška poezija; Bishop, Elizabeth; literarno prevajanje; polisemični refren; prevodi v slovenščino; Taufer, Veno; vilanela